PARENT STORY TELLING SKILL AT BAITUL MAQDIS CIPTA EDUKASI - Julaeha, Uha; Prijana, Prijana; Yanto, Andri (D3 Teknisi Perpustakaan Fakultas Vokasi Universitas Airlangga, 2019)
Background of the study: informal education can be enhanced by providing parents with parenting education (non-formal education for parents) which can be obtained through courses, training, study groups, and community learning centers in order to support lifelong education. One of them is through inspiring fairy tale training for parents and educators organized by the educational institution Baitul Maqdis Cipta Edukasi (BMCE). Purpose: This research aims to determine the differences in the ability of storytelling participants between before and after being given treatment in the form of storytelling training in Baitul Maqdis Cipta Edukasi. Method: The method in this research uses a quantitative method through a pre-experimental study approach with the form of one group pretest-posttest design. The research population consisted of 36 Baitul Maqdis Cipta Edukasi storytelling trainees. Sampling is based on the proportion of total sampling, which is a total of 36 participants. The research data was collected using primary data and secondary data. Primary data in the form of questionnaires, observation, interviews. Secondary data in the form of library studies. The research data uses a nominal scale and analyzed using a sign test (sign test) with a 95% confidence level. Findings: The results of this study indicate that there are differences in storytelling skills in the form of the ability to understand and choose story material, the ability to tell fairy tales, and the ability to tell messages behind fairy tales after being given treatment. Conclusion: So that storytelling training improves the ability of storytelling participants and there are differences in the form of additional knowledge and skill of participants.